Irrigation management methods crisphead lettuce grown in a greenhouse - Borges Valeriano, Taynara Tuany [UNESP]; Santana, Marcio Jose de; Jesus, Marcos Vinicios de; Leite, Leticia de Souza (Univ Federal Mato Grosso, 2018)
Lettuce is the main herbaceous vegetable in production and consumption of the Brazil. It is a culture dependent primarily of water, and its production in a protected environment, coupled with the use of irrigation practices, can contribute to increased yield and improved quality of vegetable. In this context and in the national water scenario the use of irrigation management techniques is essential. The current experiment was conducted in a greenhouse to evaluate the effects of irrigation established by different methods in the yield of lettuce grown in protected environment. The cultivar used was Taina, the crisphead type. The experimental design was a randomized block with 8 repetitions, 5 management methods of irrigation. Irrigation levels were established by equations Hargreaves, Blaney-Criddle, Tanque Classe A, Tanque Alternativo and Drenos Coletores. The variables evaluated were: total weight of the plant, yield (commercial weight or head), dry mass of head, number of inner leaves, head circumference, diameter and efficiency of water use. It was observed that climate methods represented by the equation Hargreaves and Blaney-Criddle outperformed the evaporimeters tanks when installed within protected environments. The greater efficiency of water use was obtained using the method Hargreaves and Blaney - Criddle, which is 0.64 and 0.67 g mm(-1), respectively.
Keywords: water use efficiency; evapotranspiration; Lactuca sativa L.; rational management